Combating highly resistant emerging pathogen Mycobacterium abscessus and Mycobacterium tuberculosis with novel salicylanilide esters and carbamates - Baranyai, Zsuzsa; Krátký, Martin; Vinšová, Jarmila; Szabó, Nóra; Senoner, Zsuzsanna; Horváti, Kata; Stolaříková, Jiřina; Dávid, Sándor; Bősze, Szilvia (European journal of medicinal chemistry, 2015)
In the Mycobacterium genus over one hundred species are already described and new ones are periodically reported. Species that form colonies in a week are classified as rapid growers, those requiring longer periods (up to three months) are the mostly pathogenic slow growers. More recently, new emerging species have been identified to lengthen the list, all rapid growers. Of these, Mycobacterium abscessus is also an intracellular pathogen and it is the most chemotherapy-resistant rapid-growing mycobacterium. In addition, the cases of multidrug-resistant Mycobacterium tuberculosis infection are also increasing. Therefore there is an urgent need to find new active molecules against these threatening strains. Based on previous results, a series of salicylanilides, salicylanilide 5-chloropyrazinoates and carbamates was designed, synthesized and characterised. The compounds were evaluated for their in vitro activity on M. abscessus, susceptible M. tuberculosis H37Rv, multidrug-resistant (MDR) M. tuberculosis MDR A8, M. tuberculosis MDR 9449/2006 and on the extremely-resistant Praha 131 (XDR) strains. All derivatives exhibited a significant activity with minimum inhibitory concentrations (MICs) in the low micromolar range. Eight salicylanilide carbamates and two salicylanilide esters exhibited an excellent in vitro activity on M. abscessus with MICs from 0.2 to 2.1 μM, thus being more effective than ciprofloxacin and gentamicin. This finding is potentially promising, particularly, as M. abscessus is a threateningly chemotherapy-resistant species. M. tuberculosis H37Rv was inhibited with MICs from 0.2 μM, and eleven compounds have lower MICs than isoniazid. Salicylanilide esters and carbamates were found that they were effective also on MDR and XDR M. tuberculosis strains with MICs ≥1.0 μM. The in vitro cytotoxicity (IC50) was also determined on human MonoMac-6 cells, and selectivity index (SI) of the compounds was established. In general, salicylanilide derivatives substituted by halogens on both salicyl and aniline rings showed better activity, than 4-benzoylaniline derivatives. The ester or carbamate bond formation of parent salicylanilides mostly retained or improved antimycobacterial potency with moderate selectivity.
Keywords: Salicylanilide; Salicylanilide 5-chloropyrazinoate; Mycobacterium; karbamáty; Mycobacterium abscessus; vztah mezi dávkou a účinkem léčiva; buněčné linie; mikrobiální testy citlivosti; Esters; Molecular Structure; Structure-Activity Relationship; lidé; Anti-Bacterial Agents; multirezistentní tuberkulóza; Cell Line; salicylanilidy; molekulární struktura; Microbial Sensitivity Tests; Dose-Response Relationship, Drug; Carbamates; Tuberculosis, Multidrug-Resistant; Multidrug-resistant Mycobacterium tuberculosis; Salicylanilide carbamate; vztahy mezi strukturou a aktivitou; estery; Antimycobacterial activity; antibakteriální látky; Salicylanilides; Humans